Buddhist practice, recreation, and fun: entanglements of popular culture and material religion - Prohl, Inken (The Routledge handbook of material religion, 2023)
As soon as the material and the body are introduced into our understanding of religion, it becomes much more entwined with what is generally termed “popular culture.” Based on current approaches to material religion, this chapter features examples from Buddhism to show how the borders between “religion” and “popular culture” are blurring and beginning to crumble and fragment. The intention is not simply to examine “Buddhism” and the points where it intersects with what we perceive as “popular culture,” such as Buddhism and entertainment, medicine or consumption, but to take a close look at examples of Buddhist practice itself, thereby offering snapshots of the many ways in which Buddhist-inspired ideas, practices, and materialities have been adopted by neighboring fields in our contemporary world. After briefly clarifying my understanding of the principles of “material religion” and the term “popular culture,” the chapter sections focus on the popular worlds of historical Buddhism, the attractions of contemporary Buddhism in Asia and the global popularity of Buddhist materialities, before presenting some reflections on the spheres that open up beyond the dichotomization between religion and popular culture. There will be particular discussion of the gender-related asymmetries causing these dichotomizations as well as of the dramatic transformation of the assumed transcendental that impacts our life.
Gesehen am 16.10.2023